Readiness of Islamic Religious Education Teachers for Digital Learning Post Pandemic Covid 19 - Agus Ruswandi; M Aditya Firdaus; Riki Ruswandi (International Journal of Ethno-Sciences and Education Research, 2023)
The consequence of the Covid 19 pandemic is an increase in the use of digital-based information technology, which also applies to education. Learning was obligated to use the internet network during the Covid 19 pandemic. Regarding the Covid 19 pandemic, digital-based learning would become a necessity for teachers and students to be able to use digital-based learning devices. Teachers and students must be able to use digital devices for learning process. But the state of the problem is whether Islamic Religious Education teachers are already ready to meet the requirements of digital learning. Therefore, It is necessary to investigate the extent to which Islamic Religious Education teachers are equipped to confront all-digital learning in the future. The purpose of this study was to investigate the preparedness of Islamic Religious Education teachers in Madrasa` for digital-based learning. This study's research method is a descriptive reserach. This study's data source is Islamic Religious Education teachers in the Madrasa` in West Java, with a 15 Madrasa and 42 teachers as source of data. According to the findings of this study, as many as 26.18% of teachers were "very capable" of using computer devices. As many as 21.43% of teachers were "very capable" of using Microsoft office. As many as 4.76% were "very ready" for e-learning on Islamic Religious Education. An average of 9.52 teachers are "very ready" to learn through video conferencing applications. Islamic Religious Education teachers are still unprepared to deal with digital-based learning. This is due to the fact that not all teachers have mastered the software applications used for learning, as well as the limited facilities available in schools to support digital-based learning. The findings of this study suggest that teachers should improve their skills in using software for e-learning and creating digital learning tools, teaching materials, and learning documents. Madrasa provide adequate facilities to support the digital-based learning process to keep up with current technological and information developments.